AKRs confer oligodendrocytes resistance to differentiation-stimulated ferroptosis - Valentina Saverio; Emanuele Ferrario; Romina Monzani; Mara Gagliardi; Francesco Favero; Davide Corà; Claudio Santoro; Marco Corazzari (Redox Biology)
Ferroptosis is a recently characterized form of cell death that has gained attention for its roles in both pathological and physiological contexts. The existence of multiple anti-ferroptotic pathways in both neoplastic and healthy cells, along with the critical regulation of iron metabolism involved in lipid peroxides (lipid-ROS) production—the primary mediators of this cell death process—underscores the necessity of precisely controlling or preventing accidental/unwanted ferroptosis. Conversely, dysregulated iron metabolism and alterations in the expression or activity of key anti-ferroptotic components are linked to the development and progression of various human diseases, including multiple sclerosis (MS). In MS, the improper activation of ferroptosis has been associated with the progressive loss of myelinating oligodendrocytes (myOLs). Our study demonstrates that the physiological and maturation-dependent increase in iron accumulation within oligodendrocytes acts as a pro-ferroptotic signal, countered by the concurrent expression of AKR1C1. Importantly, MS-related neuroinflammation contributes to the down-regulation of AKR1C1 through miRNA-mediated mechanisms, rendering mature oligodendrocytes more vulnerable to ferroptosis. Together, these findings highlight the role of ferroptosis in MS-associated oligodendrocyte loss and position AKR1C1 as a potential therapeutic target for preserving oligodendrocyte integrity and supporting neuronal function in MS patients.